Synthesis of N-Sulfonyl- and N-Acylpyrroles via a Ring-Closing Metathesis/Dehydrogenation Tandem Reaction - Chen, Weiqiang; Zhang, Yin-Lin; Li, Hui-Jing; Nan, Xiang; Liu, Ying; Wu, Yan-Chao (Synthesis, 2019)
N-Sulfonyl- and N-acylpyrroles were synthesized via olefin ring-closing metathesis of diallylamines and in situ oxidative aromatization in the presence of the ruthenium Grubbs catalyst and a suitable copper catalyst. In the presence of Cu(OTf)2 and CuBr2, the reaction afforded N-sulfonyl- and N-acylpyrroles, respectively, in one pot. Under an oxygen atmosphere, the reaction went smoothly without the need of hydroperoxide oxidants. This protocol possesses many advantages, such as using a nonhazardous oxidant and readily available starting materials, operating in one pot, and showing a broad substrate scope.
Keywords: N-substituted pyrroles; ring-closing methathesis; Grubbs catalyst; Oxydehydrogenation; tandem reactions